2016
DOI: 10.17221/326/2014-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of allele d ‒ a newly identified allele of the 1-aminocyclopropane-1-carboxylate oxidase 1 (ACO1) gene in apple - Short Communication

Abstract: Apple is a climacteric fruit of economic importance and high nutritional value. Better understanding of the apple ripening process is needed to improve fruit quality and extend apple shelf life. This paper presents the results of molecular cloning and characterization of a newly identified allele of the ripening-specific ACO1 gene from Malus floribunda 821. A polymorphism of the ACO1 gene was detected using the polymerase chain reaction and BamH1 and RsaI enzymatic digestion. Whilst cloning and sequencing data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…The amplification of the ACO1 gene by using M11 and M12 primers (Castiglione et al, 1999) resulted in a PCR product of approximately 1,600 bp (Figure 2a). The size of the PCR fragment was consistent with the ACO1 product reported for autochthonous and foreign cultivars (Marić et al, 2005a;Marić and Lukić, 2014), selections singled out at the Fruit Research Institute, Čačak (Marić et al, 2005b) and seedlings of an interspecific F1 progeny from the cross 'Fiesta' × 'Totem' (Fernández-Fernández et al, 2008) and Malus species (Marić, 2016;Marić et al, 2019). Given that a monomorphic PCR product was obtained, further identification of ACO1 alleles was based on its restriction analysis conducted by digestion with BamH1 [yielded a monomorphic fragment of 830 bp and a segregating fragment of 760 bp (f2); another segregating fragment of 700 bp (f1) was not observed] and RsaI [yielded a monomorphic fragment of 230 bp and two segregating fragments of 530 and 680 bp (considered as f1 fragment) and 1,270 bp (f2)] enzymes.…”
Section: Aco1 Genotyping Of Old Cultivars and Landracessupporting
confidence: 80%
See 4 more Smart Citations
“…The amplification of the ACO1 gene by using M11 and M12 primers (Castiglione et al, 1999) resulted in a PCR product of approximately 1,600 bp (Figure 2a). The size of the PCR fragment was consistent with the ACO1 product reported for autochthonous and foreign cultivars (Marić et al, 2005a;Marić and Lukić, 2014), selections singled out at the Fruit Research Institute, Čačak (Marić et al, 2005b) and seedlings of an interspecific F1 progeny from the cross 'Fiesta' × 'Totem' (Fernández-Fernández et al, 2008) and Malus species (Marić, 2016;Marić et al, 2019). Given that a monomorphic PCR product was obtained, further identification of ACO1 alleles was based on its restriction analysis conducted by digestion with BamH1 [yielded a monomorphic fragment of 830 bp and a segregating fragment of 760 bp (f2); another segregating fragment of 700 bp (f1) was not observed] and RsaI [yielded a monomorphic fragment of 230 bp and two segregating fragments of 530 and 680 bp (considered as f1 fragment) and 1,270 bp (f2)] enzymes.…”
Section: Aco1 Genotyping Of Old Cultivars and Landracessupporting
confidence: 80%
“…Therefore, among ACO1 alleles, A and B, firstly revealed by Castiglione et al (1999), correlate with the alleles a and b, reported by Marić and Lukić (2014), and the alleles ACO1-2 and ACO1-1, published by Costa et al (2005), as well as with the alleles c, d and n, found by Marić et al (2005b), Marić and Lukić (2014) and Marić (2016). To date, the allele d of the ACO1 gene has been confirmed only in nine wild Malus species (Marić, 2016;Marić et al, 2019).…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations